An Analysis Of Fifth-Grade Students’ Difficulties In Solving Fraction Problems Based On Newman’s Error Analysis - Niluh Lisa Arianti; Waode Ekadayanti; Ashari Usman (CV. Gerasi Insan Nusantara, 2025)
This study aims to analyze the difficulties experienced by fifth-grade students at each stage of the Newman Procedure in solving fraction word problems and to identify the factors contributing to these difficulties. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of 22 fifth-grade students who completed a written test. Five students were purposively selected as interview participants based on the variation in the difficulties they experienced, while one fifth-grade teacher served as a supporting informant. Data were collected through written tests, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing and verification. Data validity was established through technical and source triangulation. The findings showed that students did not experience difficulties at the reading stage, but difficulties were identified at the comprehension, transformation, process skills, and encoding stages. The factors contributing to these difficulties included limited understanding of problem information, confusion in connecting problem information with appropriate mathematical operations, inadequate mastery of fraction calculation procedures, and hesitation in writing the final answer. These factors are interrelated and collectively affect the overall problem-solving process. The findings are expected to provide teachers with information for designing more effective mathematics instruction based on the stages of the Newman Procedure, particularly in helping elementary school students overcome difficulties in solving fraction word problems.